The history of the Brethren - Noel, Napoleon L. 1853-1932 (Denver, CO W.F. Knapp, 1936)
Contents : vol. 2 : chapters 7-12 : . Includes bibliographical references and index to both volumes.
Copy one donated by Mr R.E. Glasgow
Keywords: Brethren movement -- Exclusive Brethren -- church history